RELEVANSI NILAI LABA AKUNTANSI AKRUAL DAN ARUS KAS OPERASI TERHADAP UNEXPECTED RETURN PADA EMITEN DI BURSA EFEK JAKARTA - ., Subagyo; Hayana, Marcellina (Akuntansi Krida Wacana, 2007)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  AbstractFinancial accounting information is used by potensial user to makenecessary economic decisions. However, with increased development,accounting information will be necessary for making important decisionsin the capital market. The objective of this research is the examining thevalue Ã¢â¬â relevance of earning, cash flow from operating activities, totalcash flow, and also the incremental of earning, cash flow from operatingactivities , and total cash flow as reported under PSAK No.2 to unexpectedreturn. The value relevance is assessed by the cash flow from operationdisclosures influencing the investment decisions. As much as 20 firmslisted in LQ 45 Index in Jakarta Stock Exchange were taken as the sampleusing provosive sampling method. that year have beed used in thisresearch are 2004, 2005 and 2006. the model examining the valuerelevance of earning, cash flow from operations, total cost and in thecremental value of them. The result of multivariate analysis on the overallsample show that earning , cash flow operation and the incremental valueof them have not relevance return in 2004, 2005, and 2006.Keywords: Earning, Cash Flow from operation and Unexpected Return